Tapping below the lateral line does not reduce maple sap yield or quality - Tim Rademacher; Stéphane Corriveau; Jessica Durand; Jessica Houde; Mustapha Sadiki; Andréanne Ouellet; Marco Gilbert; Luc Lagacé (Trees, Forests and People, 2024)
Modern maple sugaring operations use vacuum tubing systems to enhance sap flow and maximize yield. The positioning of tapholes is a crucial aspect influencing tree health and sap yields, but is limited by dropline length. Inverting droplines to expand the tappable zone and reduce the risk of over-tapping has raised concerns about vacuum efficiency and microbial contamination.We examined over 2200 trees on multiple high-vacuum 5/16″ tubing systems at two sites over three seasons, tapping at various heights above and below the lateral line. Our analysis showed no significant decrease in sap yield or sugar concentration when tapping below the lateral line. Taps at extreme heights above the lateral line produced slightly more sap (estimated at 0.6 l of sap per tap for a good production season) and marginally sweeter sap (0.06 °Brix). However, differences in vacuum management had a more significant impact on yield. Additionally, there was no evidence of increased microbial activity or changes in sap pH due to relative tapping height.These findings demonstrate that tapping below the lateral line effectively doubles the tappable zone without significantly affecting sap yield or quality, promoting sustainable maple sugaring practices by ensuring long-term productivity without compromising sap yields or quality.